The effect of reducing blood sugar levels from Stichopus hermanii on alloxan-induced rats - I Putu Gede Adi Purwa Hita; Putu Yudhistira Budhi Setiawan; Ni Kadek Dwi Sri Mahayani (Pharmaciana, 2026)
Stichopus hermanii, or gold sea cucumber, is a marine organism that can be utilized for the treatment of diabetes mellitus. The relationship between observed biological activities and the responsible bioactive compounds is influenced by the solvent used during extraction. The compounds in gold sea cucumber are suspected to reduce blood sugar levels and can dissolve in a polar solvent like water. This study aims to quantitatively evaluate the reduction in blood sugar with the administration of gold sea cucumber water extract by a pretest and posttest control group design method, where treatment groups administered gold sea cucumber water extract in each kilogram rat’s body weight at doses of 45 mg, 90 mg, and 180 mg. Before treatment, rats were induced with alloxan to get diabetic condition. Diabetic rats with blood sugar levels over 200 mg/dL were treated once daily for 28 days orally. Blood sugar levels were measured five times and then blood sugar levels were assessed analytically using the GLM-RM method. The positive control group exhibited a reduction of 84.1%, while treatment groups with doses of 45 mg, 90 mg, and 180 mg showed reductions of 72.4%, 76.7%, and 79.9%, respectively. The negative control group showed a reduction of 1.4%. Statistically significant reductions in blood sugar levels were observed in each group and time parameter (p < 0.05). It can be concluded that gold sea cucumber water extract contains bioactive compounds and effectively reduces blood sugar levels in alloxan-induced male Wistar rats (Rattus norvegicus).